Application of Information Literacy Based on English Ability: Case Study of The Information and Library Science S-1 Study Program Students, Academic Year 2013 - Jumino Jumino (Program Studi Ilmu Perpustakaan, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
The purpose of this study is to find out how the application of information literacy based on the students’ English ability of S1 Library Science Study Program Faculty of Humanities Diponegoro University of Semarang, year 2013. The research method used is descriptive qualitative with case study type. The subject of this research is the students of S1 Library Science Study Program, year 2013, and the object of English proficiency and its application for information literacy. Data collection was done by interview and document study. The informants were chosen by purposive sampling, that is, the students of S1 Library Science Study Program Faculty of Humanities Diponegoro University of Semarang, year 2013 who have got information literacy subject amount of 15 students. The result of the research shows that the students of year 2013 have used English to be literate. They understand their needs, then seek information either from international journals, via internet, or from the library. The use of their information is clear, that is, to support in writing thesis. They can overcome their lack of English language skills.